2018
DOI: 10.4252/wjsc.v10.i10.138
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of autologous stem cell transplantation for decompensated liver cirrhosis: A retrospective cohort study

Abstract: AIMTo evaluate the long-term efficacy and safety of autologous stem cell transplantation (SCT) for decompensated liver cirrhosis.METHODSConsecutive patients with decompensated liver cirrhosis were included and assigned into the SCT group and non-transplantation (non-SCT) group according to whether they received SCT treatment. Patients were followed up for ten years. The long-term survival rate and incidence of hepatocellular carcinoma (HCC) were compared between groups.RESULTSA total of 159 patients were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Therefore, systemic administration of autophagy-regulated agents is inappropriate. In recent years, stem cell therapy emerges as a promising strategy in treating chronic diseases [48, 49]. Stem cells can help repair damaged tissues or structures towards the normal state, and numerous studies have demonstrated that stem cells take effect via restoring autophagy homeostasis [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, systemic administration of autophagy-regulated agents is inappropriate. In recent years, stem cell therapy emerges as a promising strategy in treating chronic diseases [48, 49]. Stem cells can help repair damaged tissues or structures towards the normal state, and numerous studies have demonstrated that stem cells take effect via restoring autophagy homeostasis [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…There was also a higher incidence of hepatocellular carcinoma in stem cell patients (47.8% vs. 21.7%, p < 0.05). 21 Though theoretically, there is a possibility of uncontrolled malignant proliferation of an aged stem cell niche, 22 the development of hepatocellular carcinoma in a 10-year period could develop as a part of the natural history. This needs further investigation, though a close watch on the development of hepatocellular carcinoma is always required following any cell-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that pigs transplanted with stem cells into the infarcted myocardium, experienced more frequent monomorphic ventricular tachycardia, compared to the vehicle-treated group [ 2 ]. It has also been reported that cell transplantation may fail to improve the long-term efficacy and increase the incidence of hepatocellular carcinoma for decompensated liver cirrhosis [ 3 ]. Acellular scaffolds offer a relatively safe and potentially off-the-shelf solution to cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%